2013
DOI: 10.1007/s11104-013-1895-6
|View full text |Cite
|
Sign up to set email alerts
|

Proof of concept: nitrogen use efficiency of contrasting spring wheat varieties grown in greenhouse and field

Abstract: 23Aims Major aims were to test and evaluate a new concept for assessment of nitrogen use 24 efficiency (NUE) of crops by growing six spring wheat varieties in greenhouse and field 25 environments. NUE was calculated with a plant based concept integrating the entire crop life 26 history and separating plant characteristics from environmental factors affecting NUE. 27Specific hypotheses were tested related to the varieties' drought and nutrient fertilisation 28 responses for NUE components, and coherence of thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 22 publications
5
23
1
Order By: Relevance
“…A set of 24 modern wheat varieties were ranked for NUE across trial sites to reveal lines showing stable performance across environments. In line with previous reports (Bertin and Gallais 2001;An et al 2006;Asplund et al 2014), our study demonstrated that there is significant genetic variation for NUE between wheat genotypes. Abe et al (2013) also demonstrated significant genetic variation for GY and measured NUE component traits among maize hybrids at increasing rates of N application.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A set of 24 modern wheat varieties were ranked for NUE across trial sites to reveal lines showing stable performance across environments. In line with previous reports (Bertin and Gallais 2001;An et al 2006;Asplund et al 2014), our study demonstrated that there is significant genetic variation for NUE between wheat genotypes. Abe et al (2013) also demonstrated significant genetic variation for GY and measured NUE component traits among maize hybrids at increasing rates of N application.…”
Section: Discussionsupporting
confidence: 93%
“…The genetic basis for variation in NUE has been studied in NUE-Quantitative Trait Loci (QTL) studies. For example, Bertin and Gallais (2001) in a study of genetic variation for NUE in a set of maize recombinant inbred lines, found significant QTL for GY at high N and low levels of N. In addition, Asplund et al (2014) N18 N50 N64 N87 N18 N50 N64 N87 N18 N50 N64 N87 N18 N41 N87 N18 N41 N87 MIN ) and nitrogen use efficiency (NUE, kg GY kg −1 N) of 24 wheat genotypes grown with varied levels of N fertilisation at five sites in South Australia, 2010-2011. Vertical error bars represent the standard errors of the predicted means after spatial analysis spring wheat varieties under field and controlled conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The NUpE decreased with increasing N supply for the cultivar BRS Tangará, while CD 150 and TBIO Iguaçu did not change. Guarda et al (2004) and Asplund et al (2014) also reported increasing NUpE for increasing N supply levels.…”
Section: Resultsmentioning
confidence: 81%
“…Due to this fact and the possible environmental problems related to its use, the Nitrogen use efficiency (NUE) plays a fundamental role in sustainable grain production (Asplund et al 2014). NUE is given by the ratio between grain yield (GY) and the amount of nutrient provided by the fertilizer (Moll et al 1982;Cormier et al 2013;Dai et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the fact that nitrogen (N) is the most limiting nutrient for wheat production and the possible environmental problems related to its use, nitrogen use efficiency (NUE) of crops plays a fundamental role in sustainable grain production (Pan et al, 2006;Asplund et al, 2014). NUE is given by the ratio between grain yield (GY) and the amount of nutrient provided by the fertilizer (Moll et al, 1982;Cormier et al, 2013).…”
Section: Introductionmentioning
confidence: 99%